ASSESSING THE FEASIBILITY OF ONLINE BUSINESS MODELS: A COMPARATIVE STUDY - Elsa, Dea Adilla (Proceeding International Seminar of Islamic Studies, 2023)
Online business models are becoming increasingly popular in today's digital era. However, not all online business models are successful and survive in the long term. Therefore, it is important for online business owners to evaluate the feasibility of their business model before deciding to launch or develop it further. This comparative study aims to provide online business owners with insight and inspiration in evaluating their own business model, as well as considering ways to develop or improve it. The online business models discussed in this comparative study include e-commerce, subscription services, online advertising, and affiliate marketing. Each of these business models is analyzed in terms of feasibility, advantages and disadvantages.Through this comparative study, it is hoped that online business owners can understand better about how to assess the feasibility of their online business model, and make better decisions in developing their business. By understanding the uniqueness and challenges of each online business model, business owners can choose the right business model for their business and increase the chances of success in the long term. The method that can be used is through qualitative methods, namely interviewing business owners, online surveys. Such data may include information about sales levels, revenue sources and other relevant factors.